(untitled) (Journal of Management and Social Sciences, 2022)
Reward system is a veritable medium used to increase employees’ productivity. It seeks to attract and retain suitable employees, encourages good management. Employee productivity is hindered when rewards system is inadequate. The main objectives of the study were to examine the effect of reward system on employees’ productivity. This study unfolds a number of factors that account for an equitable reward system for effective performance and efficiency. The population comprises of 92 staff of the selected staff of the bank under study. Multistage sampling technique was used and 44 staff were purposefully selected for gathering data for the study. Data was collected and analyzed using frequency table and linear regression to examine the effect of reward system on employees’ productivity. Findings of the study show that there is a significant effect of reward system on employees productivity with β =.0124, .0001, p-value<0.05. This implies that an increase in the covariates increase in the reward via productivity. In view of this, the study recommends that the organizations’ reward packages should be linked to productivity, employee satisfaction and motivation. Also, organization efficiency and sustainable can be achieved through institutionalization of good reward system.